A huge gastric stromal tumor in a 13-year-old girl - Oğuzkurt, Pelin; Akçören, Zuhal; Şenocak, M. Emin; Çağlar, Melda; Büyükpamukçu, Nebil (The Turkish Journal of Pediatrics, 2002)
A 13-year-old girl presenting with severe anemia was diagnosed to have a large gastric tumor protruding toward the antrum with two central ulcerations. Partial gastrectomy including antrectomy and gastroduodenostomy were performed. Histologic and immunohistochemical studies revealed one of the most uncommon gastric tumors in children; a gastrointestinal stromal tumor. Close follow-up of the patient with endoscopy, abdominal ultrasonography and/or computed tomography in three to six month intervals revealed no recurrences or metastasis of the tumor following its complete excision.